دراسة مقارنة إدارة الكفاءة على التعلم بين خريجي المدارس الداخلية وغير الداخلية بقسم تعليم اللغة العربية - Syahril, M Alfi; Suhaimi, Suhaimi; Hayati, Salma (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2020)
The objective of the study were to find out the differences of learning management competence among Arabic Language Education Students of UIN Ar-Raniry who come from Ma'had and Non-Ma'had. The kind of this research was a comparative study. The sample of this study were students of the Arabic Language Study Program UIN Ar-Raniry starting from the class of 2015 up to the class of 2018, amounting to 228 students from a population of 837. The data collection in this study used a questionnaire. The data analysis technique used was univariate, and bivariate data analysis techniques through the independent sample 2-sample t-test technique. The results of this study indicate that: (1) There is a significant difference in learning management between Arabic Language Education Students of UIN Ar-Raniry Banda Aceh originating from Ma'had and Non-Ma'had, where the management of students' learning competencies is more advanced. better than non ma'had graduate students. (2) There are differences in the average score of each aspect of the management of learning competencies of students of Ma'had graduates and students of non-Ma'had graduates. Aspects of self-supervision (controlling) of ma'had graduate students excel with an average difference of 0.08, Aspects of organizing themselves (organizing) of ma'had graduate students excel with an average difference of 0.17, Aspects of the ability to facilitate themselves (facilitating) ma'had graduate students with an average difference of 0.13, and motivating aspects of ma'had graduate students excel with an average difference of 0.06.